Lipocalin-2 contributes to experimental atherosclerosis in a stage-dependent manner. (August 2018) - Amersfoort, J.; Schaftenaar, F.H.; Douna, H.; van Santbrink, P.J.; Kröner, M.J.; van Puijvelde, G.H.M.; Quax, P.H.A.; Kuiper, J.; Bot, I.
Abstract: Background and aims: Lipocalin-2 (Lcn2) is a glycoprotein which can be secreted by immune cells. Several studies in humans have suggested Lcn2 can be used as a biomarker for the detection of unstable atherosclerotic lesions, partly as it is known to interact with MMP-9. Methods: In this study, we generated Ldlr -/- Lcn2 -/- mice to assess the functional role of Lcn2 in different stages of atherosclerosis. Atherosclerotic lesions were characterized through histological analysis and myeloid cell populations were examined using flow cytometry. Results: We show that Ldlr -/- Lcn2 -/- mice developed larger atherosclerotic lesions during earlier stages of atherosclerosis and had increased circulating Ly6C hi inflammatory monocytes compared to Ldlr -/- mice. Advanced atherosclerotic lesions from Ldlr -/- Lcn2 -/- mice had decreased necrotic core area, suggesting Lcn2 deficiency may affect lesion stability. Furthermore, MMP-9 activity was diminished in plaques from Ldlr -/- Lcn2 -/- mice. Conclusions: Altogether, these findings suggest that Lcn2 deficiency promotes lesion growth in earlier stages of the disease while it decreases MMP-9 activity and necrotic core size in advanced atherosclerosis. Highlights: Local Lcn2 expression is increased in murine atherosclerotic lesions. Lcn2 deficiency increased atherosclerosis during early stages of the disease. Circulating inflammatory monocytes were increased in Lcn2 deficient mice during atherogenesis. Lcn2 deficiency decreased necrotic core formation in advanced lesions. Lcn2 deficiency decreased MMP-9 activity in murine atherosclerosis.